2015
DOI: 10.1108/ijpdlm-08-2013-0228
|View full text |Cite
|
Sign up to set email alerts
|

Logistics service providers and corporate social responsibility: sustainability reporting in the logistics industry

Abstract: Sustainability reporting in the logistics industry AbstractPurpose -The aim of this paper is to present a content analysis of Corporate Social Responsibility (CSR) reports published by Logistics Service Providers (LSPs), and to analyse factors influencing the level and scope of reporting. In order to address this objective, we show to what extent various social and environmental categories are covered in the CSR reports. We also investigate whether any differences in the use of CSR indicators can be found with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
109
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(122 citation statements)
references
References 67 publications
(87 reference statements)
5
109
3
Order By: Relevance
“…Corporate social responsibility is an important motivation for companies to exert efforts for social benefit [58]. To support the development of small agri-businesses, AF adopts the "online and offline model" to provide them with business loans.…”
Section: Social Objectivementioning
confidence: 99%
“…Corporate social responsibility is an important motivation for companies to exert efforts for social benefit [58]. To support the development of small agri-businesses, AF adopts the "online and offline model" to provide them with business loans.…”
Section: Social Objectivementioning
confidence: 99%
“…Impact of green actions on 3PLs' performance [3,38,40,41,56,61,[66][67][68][69][70][71][72][73][74][75][76][77][78][79][80].…”
Section: Content Analysismentioning
confidence: 99%
“…With regard to sustainability, environmental issues, in particular, appear to be the most prominent focus of more recent academic papers (Piecyk and Björklund, 2015). Recent studies on procurement and subcontracting of logistics services have found that purchasing companies place high value on the environmental performance of LSPs (Large et al, 2013;Scholtens and Kleinsmann, 2011).…”
Section: Contribution Of Lsps To the Green Supply Chainmentioning
confidence: 99%
“…The activities of logistics providers have a significant environmental as well as an economic impact, which is indicative of significant potential as yet to be exploited. Indeed, companies are increasingly finding that sustainable outputs will be more sustainable if value-adding logistics activities become sustainable themselves (Wu and Dunn, 1995), although the potential of LSPs as 'enablers' of sustainable management of the supply chain has not yet been much debated in research carried out to date (Piecyk and Björklund, 2015;Kudla and Klaas-Wissing, 2012): "outsourcing has a significant potential to increase sustainability in the supply chain as third-party logistics providers focus on improving resource utilisation and making processes more efficient" (Facanha and Horvath, 2005).…”
Section: Contribution Of Lsps To the Green Supply Chainmentioning
confidence: 99%
See 1 more Smart Citation